Determinants of Social Housing Supply: An Empirical Assessment in the Context of Vietnam - Ngo, Viet Hung; Nguyen, Thi Tuyet Dung; Ngo, Ngoc Bao (International Journal of Sustainable Construction Engineering and Technology, 2025)
The development of social housing to meet the residential needs of the population has consistently remained a strategic priority of the Vietnamese Government. As urbanization accelerates—evidenced by an urbanization rate of 44.3% reported by the Ministry of Construction—the demand for housing has increased substantially. Nevertheless, the expansion of the social housing supply has not kept pace, progressing at a notably sluggish rate. A critical issue emerges: although the Government of Vietnam has enacted a range of mechanisms and policies to support social housing development—including capital allocation and various investment incentives—the supply remains insufficient. Despite evident interest and willingness among investors to engage in this sector, the actual supply currently satisfies only approximately 20% of the prevailing demand. This study seeks to identify, analyze, and evaluate the principal factors constraining the supply of social housing in Vietnam. Utilizing a mixed-methods approach—including expert interviews, a survey of 120 respondents, and exploratory factor analysis—the study investigates 14 causal factors, including two newly proposed ones related to the capacity of construction enterprises. Among these, six factors were found to exert particularly strong influence. Based on these findings, the paper offers targeted policy recommendations to address legal, financial, and institutional barriers and to enhance the viability of the social housing market in Vietnam.